The value of interferon therapy for COVID-19 in children - L. N. Mazankova; S. G. Gorbunov; E. R. Samitova (LLC "Diagnostics and Vaccines", 2021)
The article presents a literature review, which provides data on the role of interferons in the immunopathogenesis of COVID-19 and the clinical efficacy of drugs based on recombinant interferon-alpha 2b in the treatment of children with new coronavirus infection. Shown the leading role ofinterferons as factors of the first line of defense against various viruses, including SARS-CoV-2. Numerous studies have proven the feasibility of including interferon preparations in COVID-19 therapyregimens in children, both as combinations with antiviral agents and as monotherapy.